Customer satisfaction and loyalty toward low cost carriers in Malaysia - Nurul Aflah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
The emergence of low cost carrier services has changed the fundamentals of aviation industry. The on-board services are generally removed to promote low fares. Through this new invention, the perception of customers regarding the quality, satisfaction, and loyalty of LCCs service are found to be different from full service airlines. Most of the studies done in Malaysia for LCC, focusing on the relationship between service quality and satisfaction. Therefore, the purpose of this study is to explore factors of service quality used in LCC industry that influence level of satisfaction as well as level of loyalty in Malaysia. To fulfill this study, data were collected from 221 respondents across Klang Valley area and Low Cost Carrier Terminal (LCCT). SPSS and Amos were used in data analysis to present meaningful result for this study. From the result obtained in CFA, the structural equation modelling (SEM) was performed to examine the relationship of the hypotheses developed for this study. The result revealed that there is positive and significant relationship between service quality and customer satisfaction. In addition, the result also disclosed the positive and significant relationship between customer satisfaction and loyalty.